Development of on-line UV-induced volatile species generation for selenium speciation [Se(iv) and SeCN−] by ion chromatography-inductively coupled plasma mass spectrometry in petroleum refinery wastewater. Issue 4 (13th March 2017) - Chandrasekaran, K.; Garg, Nidhi; Karunasagar, D.
Abstract : UV-irradiation of selenocyanate in the presence of formic and nitric acids gives improved vapor generation at room temperature, over hydride generation. Using this, a rapid and sensitive method has been developed for selenium speciation. Abstract : An on-line UV-induced vapor generation method has been developed that allows simultaneous conversion of selenocyanate [SeCN − ] and [Se(iv )] to volatile species for their subsequent determination by IC-ICPMS in petroleum refinery wastewater with improved detection limits. The species present in the sample were separated on an anion-exchange column using a step gradient with NaOH as the eluent, and were subsequently converted to their volatile forms by UV irradiation in the presence of a mixture of HCOOH–HNO3 followed by quantitative determination using an ICP-MS. Employing a 200 μL sample injection loop, the species separation was achieved within 7 min and with the best detection limits achieved at 0.01 μg L −1 and 0.06 μg L −1 for SeCN − and Se(iv ) respectively while the reproducibilities achieved for retention times and peak areas in the chromatograms were better than 1.3% and 5.0% respectively. The method was successfully employed to study the quantitative speciation of selenium in three petroleum refinery wastewaters with accuracy of the results obtained validated by two independent methods. Further validation was carried out by a standard addition method and also by analysing a certified reference material BCR-713, wastewater effluent. Quantitative recoveries (>95%) were observed for both Se(iv ) and SeCN − in refinery wastewater.